Pengaruh Komunikasi dan Kerja Sama Tim terhadap Efektivitas Kerja Pegawai melalui Kepuasan Kerja sebagai Variabel Intervening pada UPTD RSUD Sungai Dareh - Syifa Malika Anzanie; M. Afuan; Bayu Pratama Azka (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine and try to analyze the influence of communication and teamwork on employee work effectiveness through job satisfaction as an intervening variable at UPTD RSUD Sungai Dareh. This research is a structural equation modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample for this study were employees of UPTD RSUD Sungai Dareh. The research results found that there was a significant influence between communication and job satisfaction. There is a significant influence between teamwork and job satisfaction. There is no significant influence between communication on employee work effectiveness. There is a significant influence between teamwork on employee work effectiveness. There is a significant influence between job satisfaction and employee work effectiveness. Job satisfaction is able to mediate communication on employee work effectiveness. Job satisfaction is able to mediate teamwork on employee work effectiveness.